Sektarianisme dalam Sejarah Islam - Humaira Azzahra (JURNAL INDO-ISLAMIKA, 2019)
The presence of sects in Islamic history was initially ridden by political factors. They were born as a political stream that has a share in government power. However, over time, these schools began to stand on the level of aqidah and divinity. Each sect has its own understanding of divine principles, politics, and Islamic values. It cannot be denied that this is a global concern for Muslims because it has the potential to cause division. Among the sects recorded in the history of Islam are the Shia, Khawarij, Murji'ah, Qadariyah, Jabariyah, Mu'tazilah, Asy'Ariyah, and Maturidiyah. The importance of studying sectarianism in the history of Islam is to understand the Islamic patterns that exist in various countries so as to make us have a wiser point of view in seeing diversity in religion.